Standardization and normative data of the 48-item Yoni short version for the assessment of theory of mind in typical and atypical conditions - Isernia, Sara; Rossetto, Federica; Shamay-Tsoory, Simone; Marchetti, Antonella; Baglio, Francesca (Frontiers in Aging Neuroscience, 2023)
Introduction The Yoni task is a computerized tool assessing first-and second-order affective and cognitive Theory of Mind (ToM), accounting for the multidimensional and multi-level mentalizing features. The Italian Yoni task has been validated and standardized in its 98-item version, and a 48-item short version has been proposed for a quick digital evaluation of ToM in clinical contexts. Methods The present study aimed to test the Yoni-48’s convergent validity, correlating the tool score with the Reading the Mind in the Eyes test (ET) and Gender Test (GT), its items discrimination ability through the Classical Test Theory, and Rash model, its reliability by evaluating the internal consistency (McDonald’s ω, Cronbach’s α, Guttman’s λ2, and Guttman’s λ6) and Spearman-Brown ϱSP split-half analysis, and to provide standardization and normative data in the Italian population. Results Results suggested a good convergent validity with a statistically significant association with ET (p < 0.001), while a null correlation was observed with GT (p = 0.947). The Classical Test Theory and Rash model confirmed a good discrimination ability of the Yoni-48’s second-order affective and cognitive ToM items, while weaker discrimination capacity was registered for the first-order ToM items. The inter-item reliability was optimal for clinical purposes (ω, α, λ2, λ6 ≥ 0.90). Also, the split-half reliability was high (Spearman-Brown ϱSP = 0.90). For standardization, age and education were revealed as significant predictors of Yoni accuracy scores, except for the first-order ToM score. Instead, age was the only predictor of Yoni’s response speed score. The Italian normative data showed a high Yoni accuracy in healthy adults (mean accuracy = 0.85) and speed (mean response time = 0.92). Finally, both accuracy and response time level was balanced between the affective and cognitive components of ToM. Discussion This study supports the psychometric properties of the Yoni-48 and provides normative data for the Italian population. Further studies are needed to test the suitability of this short version for profiling the social cognition neurocognitive phenotype.